2009
DOI: 10.5539/ijbm.v4n7p139
|View full text |Cite
|
Sign up to set email alerts
|

Moderating Effects of Subordinates’Competency Level on Leadership and Organization Citizenship Behavior

Abstract: This paper seeks to examine the relationship between leadership styles and organization citizenship behavior within Malaysian companies. The main motivation for the study is to find out how a superior can achieve a greater understanding of the appropriateness of certain leadership styles when dealing with different subordinates' competency level. Although there have been several studies that explored the relationship between leadership styles and citizenship behavior, hitherto there has yet a study carried out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…There are many factors put forward in the literature that contribute to the evolution and development of OCB, which are voluntary individual extra‐role behaviors that do not fall into the in‐role job descriptions of the employee. Accordingly, research has found that OCB is related to the concepts of organizational commitment, job satisfaction, perception of organizational justice, leadership characteristics and organizational climate (Yılmaz and Giderler, ; Lee and Salleh, ).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…There are many factors put forward in the literature that contribute to the evolution and development of OCB, which are voluntary individual extra‐role behaviors that do not fall into the in‐role job descriptions of the employee. Accordingly, research has found that OCB is related to the concepts of organizational commitment, job satisfaction, perception of organizational justice, leadership characteristics and organizational climate (Yılmaz and Giderler, ; Lee and Salleh, ).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Empowerment is one of the tool to achieve the positive work behavior of subordinate, which means showing confidence on the subordinate's abilities and empowering them through the work of choice, flexible rules and thus motivating them towards certain goal through various means of motivation. This results in employee devotion and hard work to achieve the mutual goals which are beneficial for both the organization and their top manager (Lee, 2009). Sometime individuals are talented and experienced and usually show high performance level but their behavior to colleagues and their supervisors is harsh and rude which causes negative impact on the work output and can act as hindrance towards achievement of organizational goals and objectives (Veiga, 1988).…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is a known fact that a person labeled as subordinate is viewed as an individual with fewer capabilities as compared to his/her boss (Konst et al, 1999). Giving authority or empowerment to subordinates and showing confidence on them increases their competency level and results in subordinate hard work and devotion to organization which lead to organizational effectiveness and success (Lee, 2009). The performance and action of both managers and subordinate are interlinked with each other.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to fulfill the purpose of the study, questionnaire technique was chosen as data gathering method since it provides certain advantages as convenience, accessibility and minimal costs (Lee & Salleh, 2009). The scales used in the study were explained below (see Table 2).…”
Section: Instrumentsmentioning
confidence: 99%